The Significance of Hydrogen Sulfide for Arabidopsis Seed Germination - Baudouin, Emmanuel; Poilevey, Aurélie; Hewage, Nishodi Indiketi; Cochet, Françoise; Puyaubert, Juliette; Bailly, Christophe (Frontiers in Plant Science, 2016)
Hydrogen sulfide (H2S) recently emerged as an important gaseous signaling molecule in plants. In this study, we investigated the possible functions of H2S in regulating Arabidopsis seed germination. NaSH treatments delayed seed germination in a dose-dependent manner and were ineffective in releasing seed dormancy. Interestingly, endogenous H2S content was enhanced in germinating seeds. This increase was correlated with higher activity of three enzymes (L-cysteine desulfhydrase, D-cysteine desulfhydrase and β-cyanoalanine synthase) known as sources of H2S in plants. The H2S scavenger hypotaurine and the D/L cysteine desulfhydrase inhibitor propargylglycine significantly delayed seed germination. We analyzed the germinative capacity of des1 seeds mutated in Arabidopsis cytosolic L-cysteine desulfhydrase. Although the mutant seeds do not exhibit germination-evoked H2S formation, they retained similar germination capacity as the wild-type seeds. In addition, des1 seeds responded similarly to temperature and were as sensitive to ABA as wild type seeds. Taken together, these data suggest that, although its metabolism is stimulated upon seed imbibition, H2S plays, if any, a marginal role in regulating Arabidopsis seed germination under standard conditions.